Which Tech Will I Use? Trends in Studentsâ Use and Ownership of Technology in a Thai University, an Ongoing Study - Yuwanuch Gulateee; Jeremy Pagram; Babara Combes (LPPM ITB, 2018)
Studentsâ ownership of technology devices, their access to software and Web-based utilities, and their related preferences are the subject of this ongoing research. The devices that instructors use in the classroom, how students use online learning systems as provided by the university, and studentsâ skill levels when using technology for learning are also included. The major objective of this research is to provide a long-term comparative analysis across one university to determine if studentsâ and lecturersâ use of technology for teaching-learning has changed. Such ongoing data collection and analysis will inform individual institutions about online learning and how to improve facilities for both staff and students for maximum educational success. An initial study was conducted in 2015. This paper reports on the second data collection to determine if there have been any changes over a two-year period. The findings indicate that students have intermediate skill levels when using basic software programs for their study, whereas their social media skills are advanced. Students use mobile devices (phones and tablets) to access online learning materials. Overall, most students and staff lack basic knowledge in using information technology for study purposes. It was concluded that the university should continue to conduct ongoing monitoring and evaluation of studentsâ and staffâs information technology competencies.